2017
DOI: 10.1017/s0140525x16000455
|View full text |Cite
|
Sign up to set email alerts
|

Explanations for attractiveness-related positive biases in an evolutionary perspective of life history theory

Abstract: The mating-related evolutionary explanation that Maestripieri et al. offer does not apply to (1) infants' positive biases toward attractive individuals and (2) adults' positive biases toward attractive infants and children. They are best understood when integrated into an evolutionary life history framework. I argue that the life history of positive biases toward attractive individuals is driven by fundamental trade-offs made throughout development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…In fact, participants may pay more attention to the opposite gender due to the biological purpose of reproduction 78 , 79 . However, the evolutionary byproduct explanation supports the idea that attractiveness preference evolved into a cross-gender feature as socialization became more complex and then turned into an indicator of overall quality 80 , 81 . Although it is not the main concern, our study suggested that the gender of participants and expressers does not obviously change the role of makeup on emotional contagion in Experiment 1 (see Supplementary Analysis 3 ).…”
Section: Discussionmentioning
confidence: 70%
“…In fact, participants may pay more attention to the opposite gender due to the biological purpose of reproduction 78 , 79 . However, the evolutionary byproduct explanation supports the idea that attractiveness preference evolved into a cross-gender feature as socialization became more complex and then turned into an indicator of overall quality 80 , 81 . Although it is not the main concern, our study suggested that the gender of participants and expressers does not obviously change the role of makeup on emotional contagion in Experiment 1 (see Supplementary Analysis 3 ).…”
Section: Discussionmentioning
confidence: 70%
“…其二, 择偶是繁殖的需要. 从纵 向看, 该理论只能解释成年人对高面孔吸引力异性的 偏好, 但不能涵盖整个生命史框架, 比如婴幼儿对高吸 引力成人面孔的偏爱和成人对高面孔吸引力婴幼儿的 偏爱 [60] . 从横向看, 个体在某方面的总体"市场价值 (market value)"是对一个人各种特质的综合表征, 但 "配偶价值(mate value)"仅仅是对个体的繁殖相关特质 的表征 [61] .…”
Section: 容貌能反映出个体在能力和禀赋上的差异 具有出众unclassified